Subsidios a la producción y delegación de la política comercial en una unión aduanera - Méndez-Naya, José (Estudios de Economía, 2016)
By using a reciprocal dumping model, this paper justifies the existing preferentialtrade agreements as being a reaction to a third country export subsidy. On theother hand, assuming that one of the member countries may set its productionsubsidies optimally, the effects on welfare derived from the delegation of customsunion’s commercial policy are addressed. The main result obtained is that in anon-transferable utility context the union is not sustainable.